2022
DOI: 10.3389/fsurg.2022.840070
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Effectiveness of Uniportal-VATS Lobectomy Compared to Open Surgery in Early-Stage Lung Cancer

Abstract: BackgroundAlthough the feasibility and safety of Uniportal-Video-Assisted thoracic surgery (U-VATS) has been proven, its surgical effectiveness is still debated. The aim of this study is to assess the equivalence of the U-VATS approach compared with an open technique in terms of surgical (nodal-upstaging, complications, and post-operative results) and short-term survival outcomes.MethodsThe clinical data of patients undergoing lobectomy for NSCLC at our center, from January 2014 to December 2019, were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…In recent years, numerous studies have shown that surgical treatment provides a remarkably improved 5-year survival rate for stage I or stage II lung cancer patients compared to those undergoing other treatments (17)(18)(19). Therefore, surgery could also be considered to be a promising treatment for some limited-stage lung cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous studies have shown that surgical treatment provides a remarkably improved 5-year survival rate for stage I or stage II lung cancer patients compared to those undergoing other treatments (17)(18)(19). Therefore, surgery could also be considered to be a promising treatment for some limited-stage lung cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Pain itself is multifactorial, and difficult to study and treat due to its subjective and unpredictable nature [ 27 ]. Minimally invasive surgery such as the uniportal VATS lobectomy for the treatment of early-stage lung cancer has led to less postoperative pain and shorter in-hospital stay [ 30 ]. However, even after minimally invasive thoracic operations, some patients suffer from chronic complaints, although they are less frequent and of lower intensity compared to thoracotomy [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last 6 years, the VATS approach and, in particular, Uniportal-VATS has become the preferred technique for all major thoracic procedures in our department [ 14 ]; therefore, urgent mediastinal and pleural toilette in cases of DNM started to be performed through this approach.…”
Section: Discussionmentioning
confidence: 99%